Career intervention effectiveness and motivation: blended and distance modalities comparison - Sílvia Monteiro; Filipa Seabra; Sandra Santos; Leandro S. Almeida; Ana Tomás de Almeida (Revista de Estudios e Investigación en Psicología y Educación)
This study evaluates the effectiveness of an intervention program on career resources in the blended and distance modalities and explores the relationship between changes in career resources and self-determined motivation. For this purpose, two groups of 68 and 72 higher education students participated in blended and distance career interventions, respectively. The blended program took place in a curricular infusion context, and was subject to assessment, while the distance program was fully voluntary. Students were assessed with pre- and post-tests regarding four career resources’ dimensions.  Motivation over program experience was assessed after the intervention. The results indicate that despite some differences between the two modalities, both career interventions were effective, with gains in three of the four assessed career resources’ dimensions. Relatedness was higher in the blended format of the program, while participants in the distance format reported experiencing higher levels of autonomy during the program. Despite that, motivation variables did not present a relevant predictive power in career resources’ gains obtained through participation in the program. Implications for practice include the possibility of infusing the program into curricula of higher education degrees as a way of increasing program completion and reaching different audiences and highlighting the importance of using multiple approaches to broaden its reach.